The recombinant subunit vaccine encapsulated by alginate-chitosan microsphere enhances the immune effect against Micropterus salmoides rhabdovirus - Xu, Fei-Fan (Journal of fish diseases, 2022)
© 2022 John Wiley & Sons Ltd.